PREFACE : 3rd International Conference on Manufacturing, Optimization, Industrial and Material Engineering (MOIME 2015). Issue 1 (29th May 2015) - Lumban Gaol, Ford; Webb, Jeff; Ding, Jun
Abstract : The 3rd International Conference on Manufacturing, Optimization, Industrial and Material Engineering (MOIME 2015) was held at the Sheraton Kuta, Bali, Indonesia, from 28 - 29 March 2015. The MOIME 2015 conference is aimed to bring together researchers, engineers and scientists in the domain of interest from around the world. MOIME 2015 is placed on promoting interaction between the theoretical, experimental, and applied communities, so that a highlevel exchange is achieved in new and emerging areas within Material Engineering, Industrial Engineering and all areas that relate to Optimization. We would like to express our sincere gratitude to all in the Technical Program Committee who have reviewed the papers and developed a very interesting Conference Program, as well as the invited and plenary speakers. This year, we received 99 papers and after rigorous review, 24 papers were accepted. The participants come from eight countries. There were four parallel sessions and two invited speakers. It is an honour to present this volume of IOP Conference Series: Materials Science and Engineering (MSE) and we deeply thank the authors for their enthusiastic and high-grade contributions. Finally, we would like to thank the conference chairmen, the members of the steering committee, the organizing committee, the organizing secretariat and the financial support from the conference sponsors that allowed the success of MOIME 2015. The Editors of the MOIME 2015 Proceedings Dr. Ford Lumban Gaol Jeff Webb, Ph.D Prof. Jun DING, Ph.D